Tight junction protein claudin-1 is differentially expressed in craniopharyngioma subtypes and indicates invasive tumor growth. Issue 2 (4th December 2013) - Stache, Christina; Hölsken, Annett; Fahlbusch, Rudolf; Flitsch, Jörg; Schlaffer, Sven-Martin; Buchfelder, Michael; Buslei, Rolf
Abstract: Background: Claudins are tight junction proteins expressed in epithelial tissues that play important roles in cell polarity and adhesion. Altered distribution of claudin-1(CLDN1) affects cell mobility and tumor invasiveness. Craniopharyngiomas (CPs) represent epithelial tumors of the sellar region, consisting of adamantinomatous (adaCP) and papillary (papCP) variants. Their tendency to infiltrate surrounding brain structures complicates successful surgery. Reliable markers are required to predict tumor behavior and to establish individualized treatment protocols. Methods: We describe the distribution pattern of CLDN1 in a large cohort of 66 adaCPs, 21 papCPs, and 24 Rathke`s cleft cyst (RCC) cases using immunohistochemistry. CLDN1 mRNA levels were analyzed with qRT-PCR in 33 CP samples. The impact on the migration potential was studied in primary adaCP cell cultures ( n = 11) treated with small interfering RNA (siRNA) for CLDN1. Furthermore, CLDN1 distribution patterns and expression levels were compared between invasive ( n = 16) and noninvasive ( n = 17) tumor groups. Results: PapCPs and RCCs exhibited a distinct homogenous and membranous expression pattern, whereas CLDN1 immunoreactivity appeared weaker and more heterogeneous in adaCPs. In the latter cases, whirl-like cell clusters showed complete absence of CLDN1. mRNA analysis confirmed reduced CLDN1 levels in adaCPs versus papCPs. Interestingly, invasive tumors exhibited significantly lower CLDN1 expression compared with noninvasive counterparts regardless of CP subtype. Accordingly, siRNA treatment for CLDN1 altered tumor cell migration in vitro. Conclusion: CLDN1 represents a novel marker in the differential diagnosis of CP variants and RCCs. Low CLDN1 expression levels correlate with an invasive CP growth pattern and may serve as a prognostic marker.